Albino wild boar (Sus scrofa) in Tamil Nadu, Southern India - Samson, Arockianathan; Krishnakumar, Nagarajan; Ramakrishnan, Balasundaram; Leona Princy, Jabamalainathan (Therya Notes, 2021)
Albinism is a hypo-pigmentary disorder with a total lack of melanins in hairs, eyes, and skin due to the heritable absence of functional tyrosinase enzyme in pigment cells affecting all skin and hairs, resulting in a total white fur with red eyes. On 10th August 2019, 11:30 am during a fieldwork we recorded an albino male wild boar in Sathyamangalam Tiger Reserve, Eastern Ghats, Tamil Nadu, Southern India. Unfortunately, numerous records of this kind of colour aberrations were not reported properly. In this note we highlight the importance of photographs as an important tool for documentation about natural history. This observation is limelight into the scientific community to better recognizing this phenomenon and the insights into the ecological and physiological implications of this situation, which has a major influence on animal survival.